Waking the rainbow dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2018)
Drake has a dream about a new dragon that is somehow trapped in a cave, so Drake, Ana and their two dragons set off to find the Rainbow Dragon's dragon master, Obi, and together they must rescue Rainbow dragon, Dayo, from Kwaku, a giant spider, who spins a deadly web.